최근 중국의 초미세먼지 오염 연구 동향 - 김유미; 김진영; 이승복; 문길주; 배귀남 (한국대기환경학회, 2015)
The Korea Ministry of Environment has established an air quality standard for PM2.5 in 2012 and it is effective from January 2015. In this study, we review various aspects of PM2.5 in China, including its measurement, modeling, source apportionment, and health effect, and suggest future research directions for PM2.5 studies in Korea. Measurements studies for PM2.5 have examined organic marker compounds and 14C as well as inorganic aerosols for distinguishing sources. Modeling results supported that the control of PM2.5 pollution in big city needs effective cooperation between city and its surrounding regions. The major PM2.5 sources in China have been identified to be secondary sulfur, motor vehicle emissions, coal combustion, dust, biomass burning, and industrial sources, however, they have seasonal dependency. Especially, the severe haze pollution event during January 2013 over eastern and northern China was driven to a large extent by secondary aerosol formation. Short-term exposure to PM2.5 is strongly associated with the increased risk of morbidity and mortality from cardiovascular and respiratory diseases, as well as total non-accidental mortality. Considered previous PM2.5 studies in China, analysis of specific organic species using online measurement, chamber experiment for secondary aerosol formation mechanism, and development of parameterizing this process in the model are needed to elucidate factors governing the abundance and composition of PM2.5 in Korea.